Lignin Unlocks Stealth Carbon Sinks in Cold Seeps via Microbial Enzymatic Gatekeeping - Jialing Li; Jingchun Feng; Pandeng Wang; Mengzhuo Zhu; Yongji Huang; Ying Wu; Junning Fan; Junlin Hu; Xiyang Dong; Yingli Zhou; Xuanyu Tao; Si Zhang (Research)
Cold seep ecosystems serve as critical hubs in marine carbon cycling through methane emissions and organic matter processing. While terrestrial lignin constitutes a major fraction of persistent organic carbon in cold seep sediments, its microbial transformation pathways in deep-sea cold seep environments remain unexplored. Here, we present the first comprehensive analysis of lignin distribution across sediment horizons at the Haima cold seep, coupled with a multi-omics investigation of microbial lignin metabolism. Laboratory enrichment of sediment communities employing lignin as the exclusive carbon substrate revealed substantial microbial community restructuring dominated by Burkholderiales, Pseudomonadales, and Rhizobiales lineages. Integrated omics resolved 2-tiered metabolic cascades: (a) enzymatic depolymerization via dyP-type peroxidases and LigEFG-mediated β-aryl ether cleavage, targeting syringyl and diarylpropane subunits; (b) funneling of aromatic intermediates through 4,5-/3,4-PDOG (protocatechuate dioxygenase) pathways into central carbon metabolism. Although direct methanogenesis was undetected, methylotrophic potential was evidenced through methane cycle gene expression patterns by lignin decomposers. Phylogenetic surveys further demonstrated the global prevalence of lignin decomposers across 12 major cold seep systems. These decomposers showed marked divergence in enzymatic repertoires compared to degraders from other ecosystems. Our findings establish 3 paradigm shifts: (a) The turnover rates of terrestrial organic carbon are likely underestimated in deep-sea ecosystems; (b) microbial consortia employ combinatorial enzymatic strategies distinct from terrestrial decomposition regimes; (c) methyl shunting from lignin breakdown primes methanogenic precursors, revealing cryptic linkages between refractory carbon cycling and greenhouse gas reservoirs.